Modelling ubiquity for second language learning. (12th April 2010) - Read, Timothy; Barcena, Elena; Rodrigo, Covadonga
Distance second language learning is essentially practical and skill-based requiring personal, social and occupational language-mediated activities with other speakers using the target language. Computer technology has long been used to try to overcome the challenges of distance learning although with limited success. To improve this situation, the authors developed a theoretical framework for second language learning that combined a cognitive student model with a collaborative group model. As the underlying access to information and computational resources becomes more ubiquitous, the framework is less able to represent how a specific computing device and real-world context mediate the selection and structuring of materials and activities, therefore, limiting the framework's effectiveness for second language learning. Hence, the existing models need to be complemented with a functional ubiquity model, which characterises the way in which the degree of ubiquity defines the types of learning activities and resources available in the framework.